Curriculum Management Of P5RA In The Democracy Project At MTsN 6 Jombang - Ahmad Fikri Ramadhan; Nur ‘Azah (International Journal of Interdisciplinary Research, 2026)
Limited teacher understanding, weak team coordination, and the absence of a systematic curriculum management pattern are the main obstacles to the implementation of the Pancasila and Rahmatan lil Alamin Student Profile Strengthening Project (P5PPRA) with the theme Voice of Democracy in madrasas. This study aims to analyze in-depth the management of the Independent Curriculum at MTsN 6 Jombang, including the planning, implementation, and evaluation stages, as well as identifying supporting and inhibiting factors. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation with the madrasah principal, deputy head of curriculum, coordinators, facilitators, and students. The results show that curriculum management is implemented in a structured and flexible manner, with the integration of Pancasila and moderate Islamic values ​​through contextual project-based learning, such as market days and democratic decision-making simulations. Supporting factors include adequate facilities, full support from the madrasah community, and close collaboration between parties. Psychological barriers between teachers and students can be overcome through intensive mentoring. This research contributes theoretically to the field of curriculum management in Islamic education by offering a character project management model based on the integration of national and religious values ​​that is applicable and can serve as a practical reference for other madrasahs. The research findings indicate that adaptive and collaborative curriculum management can increase student engagement, strengthen character, and develop social skills relevant to real life